The intakes of vitamin d and zinc and the menstrual periods of the high-school adolescent girls - Sunarto Tetes Lugito; Dono Indarto; Diffah Hanim (Alma Ata University Press, 2018)
ABSTRAKLatar belakang: Menstruasi adalah salah satu proses fisiologis dalam pertumbuhan dan perkembangan sistem reproduksi remaja putri yang membutuhkan asupan zat gizi yang memadai. Zinc digunakan sebagai kofaktor pada reseptor estrogen dan progestron sedangkan vitamin D belum diketahui fungsinya dalam mengatur siklus menstruasi. Tujuan: Untuk menganalisis hubungan antara asupan vitamin D dan zinc dan durasi menstruasi pada remaja putri. Metode: Sebanyak 154 remaja putri kelas X dan XI dari dua SMA di Kabupaten Sukoharjo, Jawa Tengah berpartisipasi dalam studi cross-sectional ini. Subjek penelitian dipilih menggunakan teknik purposive sampling dengan kriteria inklusi: usia 15-18 tahun dan tidak sedang menstruasi. Data antropometri dikumpulkan dengan pengukuran berat badan (kg) dan tinggi badan(m) sedangkan asupan vitamin D dan zinc diperoleh menggunakan kuesioner food recall 24 jam dalam 3 hari bergantian. Uji chi-square dan regresi logistik ganda digunakan untuk menganalisis variabel penelitian dengan nilai signifikansi <0,05. Hasil: Semua remaja putri memiliki asupan vitamin D yang tidak adekuat dan 89% diantaranya memiliki asupan zinc yang tidak adekuat. Durasi menstruasi yang panjang terjadi pada 8,4 % remaja putri. Asupan vitamin D yang kurang (OR=4,57; 95% CI = 0,943-22,154; p=0,059) memperpanjang durasi menstruasi sedangkan dan asupan zinc yang kurang (OR=0,247; 95% CI=0,073-0,835; p=0,024) memperpendek durasi menstruasi, dibandingkan dengan asupan vitamin D dan zinc yang cukup pada remaja putri. Kesimpulan: Asupan vitamin D yang kurang meningkatkan durasi menstruasi tetapi asupan zinc yang kurang justru menurunkan durasi menstruasi remaja putri SMA di Kabupaten Sukoharjo. Edukasi gizi di perlukan untuk meningkatkan asupan mikronutrien untuk mempertahankan durasi menstruasi. KATA KUNCI : asupan vitamin D, asupan zinc, menstruasi, remaja putri.ABSTRACTBackground: Menstruation is one of the physiological processes on growth and development of the reproductive system in adolescent girls who need adequate nutrient intake. Zinc is used as a cofactor for estrogen and progestron receptors, while vitamin D has not been known to regulate the menstrual cycle. Insufficient food intake can interfere with the duration of menstruation. Objectives: To analyse the relationship between the intakes of vitamin D and zinc and the menstrual periods of the adolescent girls.Methods: A total of 154 tenth- and eleventh-grade girl students from two senior high schools in Sukoharjo Regency, Central Java participated in this cross-sectional study. They were chosen using purposive-sampling technique with the following inclusion criteria: age of 15-18 years and not menstruating. The anthropometric data were collected by the measurement of Body Weight(kg) and Body Height (m) while the data of vitamin D and zinc intakes were obtained using a 24-hour-food-recall questionnaire in 3 alternating days. Chi-square test and multiple logistic regression were used to analyse the research variables with the significance value of < 0.05. Results: All adolescent girls had inadequate vitamin D intake and 89% of them had inadequate zinc intake. Long menstrual duration occurred in 8.4% of the adolescent girls. The deficient intake of vitamin D (OR = 4.57. 95% CI = 0.943-22.154; p = 0.059) lengthened the menstrual period whereas deficient zinc intake, (OR = 0.247. 95% CI = 0.073-0.835; p = 0.024) shortened it compared with adequate vitamin D and zinc intakes in adolescent girls.Conclusions: The deficient intake of vitamin D increases the menstrual duration, but the deficient intake of zinc actually lowers the menstrual period of high-school girls in Sukoharjo Regency. Nutritional education is needed to increase micro-nutrient intakes to maintain menstrual duration. KEYWORDS: adolescent girls, menstruation, vitamin D intake, zinc intake.